English for presentations : express series - Grussendorf, Marion (Oxford University Press, 2007)
English for Presentations provides learners with the language and techniques to help them present effectively in English. English for Presentations has six units which cover the language and skills involved at each stage of a presentation. Other related topics are also addressed, such as dealing with nervousness and interacting with an audience. Each unit includes authentic excerpts from presentations with listening activities, gap-fills, and exercises to help students learn and practise specific expressions and structures.